2020
DOI: 10.31557/apjcp.2020.21.12.3619
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CYP2D6 Polymorphisms in Determining Response to Tamoxifen in Metastatic Breast Cancer Patients: Review and Egyptian Experience

Abstract: Background: Metastatic breast cancer (MBC) represents a major health problem in Egypt and worldwide. Prognostic and predictive factors for patients with MBC are highly required for better management and improved survival. The aim of this study was to assess the prognostic and predictive value(s) of CYP2D6 polymorphisms in Tamoxifen responders and non-responders. Methods: A cohort of 157 hormone receptor positive, locally recurrent inoperable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A prospective cohort study in 157 Egyptian metastatic breast cancer patients investigated the influence of CYP2D6 polymorphisms on tamoxifen response after 6 months of tamoxifen treatment. Thirty carriers of CYP2D6 variant alleles had progression within 6 months after the start of tamoxifen treatment, whereas fourteen patients achieved good clinical tamoxifen response after 6 months [88]. This suggests that patients with metastatic breast cancer carrying certain CYP2D6 variant alleles have worse 6-month prognosis after tamoxifen treatment.…”
Section: Positive Association Cyp2d6 Genotype and Outcomementioning
confidence: 98%
“…A prospective cohort study in 157 Egyptian metastatic breast cancer patients investigated the influence of CYP2D6 polymorphisms on tamoxifen response after 6 months of tamoxifen treatment. Thirty carriers of CYP2D6 variant alleles had progression within 6 months after the start of tamoxifen treatment, whereas fourteen patients achieved good clinical tamoxifen response after 6 months [88]. This suggests that patients with metastatic breast cancer carrying certain CYP2D6 variant alleles have worse 6-month prognosis after tamoxifen treatment.…”
Section: Positive Association Cyp2d6 Genotype and Outcomementioning
confidence: 98%
“…The remaining studies on OS were not included in the meta-analysis because they did not provide HR (Ref. 49 ) or with different comparing groups (Refs 25 , 40 , 41 , 67 , 73 ). In which, significant shorter OS was found in PMs compared with EMs ( P = 0.01), and in CYP2D6*10 variant genotype (T/T) carriers compared with wild genotype (C/C) plus heterozygous genotype (C/T) carriers ( P = 0.015) (Ref.…”
Section: Resultsmentioning
confidence: 99%
“…75 A recent study on Egyptian patients with metastatic breast cancer and treated with tamoxifen demonstrated that patients who were refractory to tamoxifen therapy had CYP2D6 *3 and *4 polymorphisms whereas patients carrying the variants *10/*10 and *10/*3 of CYP2D6 were more common in the responders to the treatment with tamoxifen. 22…”
Section: Discussionmentioning
confidence: 99%